ENHANCING COMMUNICATIVE COMPETENCE OF PHILOLOGY STUDENTS THROUGH AUTHENTIC ENGLISH MATERIALS (SCIENCE TIME JOURNAL, 2026)
Nowadays, developing communicative competence has become a key goal in English language teaching, especially for students in philology faculties who are expected to use language effectively in both academic and real-life contexts. This paper looks at how authentic English-language materials can support this process. Drawing on a range of theoretical and empirical studies, it examines the role of authentic input in helping learners develop not only grammatical knowledge but also sociolinguistic, pragmatic, and strategic aspects of communication. The review suggests that authentic materials – such as media texts, conversations, and everyday language samples – can  make learning more engaging and meaningful by bringing real-world language into the classroom. They also appear to help students better understand cultural context and use language more appropriately in different situations. At the same time, the literature points out certain challenges, including the difficulty of selecting materials that match learners’ proficiency levels and the need for careful guidance from teachers.Overall, the paper argues that authentic materials can play a valuable role in developing communicative competence when they are used thoughtfully and adapted to learners’ needs. Their integration into classroom practice may help bridge the gap between theoretical knowledge and actual language use.